FLT PET/CT imaging of metastatic prostate cancer patients treated with pTVG-HP DNA vaccine and pembrolizumab. Issue 1 (30th January 2019) - Scarpelli, Matthew; Zahm, Christopher; Perlman, Scott; McNeel, Douglas G.; Jeraj, Robert; Liu, Glenn
Abstract : Background: Immunotherapy has demonstrated remarkable success in treating different cancers. Nonetheless, a large number of patients do not respond, many respond without immediate changes detectable with conventional imaging, and many have unusual immune-related adverse events that cannot be predicted in advance. In this exploratory study, we investigate how 3′-Deoxy-3'- 18 F-fluorothymidine (FLT) positron emission tomography (PET) measurements of tumor and immune cell proliferation might be utilized as biomarkers in immunotherapy. Methods: Seventeen patients with metastatic castrate resistant prostate cancer were treated with combination pTVG-HP DNA vaccine and pembrolizumab. Patients underwent baseline and 12-week FLT PET/CT scans. FLT PET standardized uptake values (SUVs) were extracted from tumors, non-metastatic lymph nodes, spleen, bone marrow, pancreas, and thyroid to quantify cell proliferation in these tissues. Regional immune cell responses to pTVG-HP DNA vaccine were assessed by comparing FLT uptake changes in vaccine draining and non-draining lymph nodes. Cox proportional hazards regression was utilized to relate FLT uptake and other clinical markers (PSA and tumor size) to progression-free survival. Area under receiver operating characteristic (AUC) curves and concordance indices were used to assess the predictive capabilities of FLT uptake. Results: Changes in FLT uptake in vaccine draining lymph nodes were significantly greater than changes in non-draining lymph nodes ( P  = 0.02), suggesting a regional immune response to vaccination. However, the changes in FLT uptake in lymph nodes were not significantly predictive of progression-free survival. Increases in tumor FLT uptake were significantly predictive of shorter progression-free survival (concordance index = 0.83, P  < 0.01). Baseline FLT uptake in the thyroid was significantly predictive of whether or not a patient would subsequently experience a thyroid-related adverse event (AUC = 0.97, P  < 0.01). Conclusions: FLT PET uptake was significantly predictive of progression-free survival and the occurrence of adverse events relating to thyroid function. The results suggest FLT PET imaging has potential as a biomarker in immunotherapy, providing a marker of tumor and immune responses, and as a possible means of anticipating specific immune-related adverse events. Trial registration: NCT02499835 .